(3MGTjI GddGQj Ydi TQM GdbGVj ejQ Ydi gOGjI GdMceIs - (3GddGQj, eUdM GdOjf, eUdM GdOjf GddGQj, eMeO Hf UdGM Hf LdGd GdedJhj GdCfUGQj, J (B979(3g` (B1571(3es ((3GhSWGf dG aj GdeOQSI Hd aj chd GdabgGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj JNdU HgOGjI MceJg MhGTj bdhHfG Yf ZhGTj GdQjhH (B... (3bhdg GYde Cf GdMceI Yde HCMhGd CYjGf GdehLhOGJ(B. (3Cbhd(B: (3ddefGXQjfs
(3BNQgG (B:s
(3BNQgG(B: (3Ke YeehG GYJHGQgG aj SGFQ GdCLSGe gPG GdGYJHGQ eHfj Ydi GdCehQ GdYQajI hdG JMbjb ajg dCf cQg GdCQV djSJ dgG TjA ef GdLgGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 169s
(3cTa GdXfhf, L (B2: 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs